Pengawasan Infrastruktur Jalan Pada Dinas Pekerjaan Umum Dan Penataan Ruang (Pupr) Di Kabupaten Bone - Fatimah, Fatimah; Sudarmi, Sudarmi; Yusuf, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine how preventive supervision in road infrastructure and repressive supervision in infrastructure at the Public Works and Spatial Planning Office in Bone Regency. This study usesd descriptive qualitative research. The number of informants in this study amounted to 12 people. Data collection techniques were observation, interviews, and documentation. The results showed that preventive supervision on road infrastructure development in Bone Regency had been maximal, because the Public Works agency had supervised activity planning in accordance with implementation / planning standards with good cooperation with consultants / service providers, but on repressive supervision of development. road infrastructure in Bone Regency had not been maximal, because when doing the inspection the problem was not punc, this was because there was missing in data collection which was used as the main basis for conducting inspections, then in conducting supervision with each of their duties. according to the field, the problem was the distance to an area was very far so it took a long time.Keywords: supervision, road infrastructure, public works and spatial planning